Interpreting the Environment: Documentation and Peculiarities (Italian-Spanish) - González Vallejo, Rubén (2021)
The environment is postulated as an innovative discipline that encompasses numerous branches that make it difficult to precisely delimit terminology. In this respect, this article aims to lay the foundations for the importance of documentation in interpretation in specialized contexts such as the environment in the Italian-Spanish combination. Initially, the state of the art will be introduced through the environmental legislation in Spain and Italy and its multidisciplinary feature. Later, the interpreter's competence in specialized contexts and the linguistic peculiarities of the environment will be introduced. Finally, the importance of the documentary phases in interpretation will be introduced together with a practical proposal based on the XI Congreso Ibérico de Gestión y Planificación Del Agua, in order to present the different documentary phases in the development of the profession.